Meningkatkan Aktivitas dan Hasil Belajar PKn melalui Value Clarification Technique Siswa Kelas V SDN 12 Gedong Tataan, Pesawaran Tahun Pelajaran 2022/2023 - Rahmah, Siti (Program Studi PGSD, Jurusan Ilmu Pendidikan, STKIP PGRI Bandar Lampung, 2023)
This classroom action research started from a background of low activity and learning outcomes for Civics students in grade V SDN 12 Gedong Tataan, Gedong Tataan District. This study uses a learning model approach to act with value clarification technique (VCT) Image Analysis. The research conducted at SDN 12 Gedong Tataan, Gedong Tataan District, aims to increase the activities and learning outcomes of Civics students in grade V and to increase the creativity and performance of teachers in learning activities. This study used a reflective and collaborative classroom action research design carried out in 3 cycles. The data were obtained through observing student activities and learning outcomes in each cycle which were analyzed descriptively quantitatively. The results of the study can be concluded that the use of the learning approach to act in this type of value clarifying technique or Value Clarification Technique of Value Analysis in the form of image analysis can increase the activities and learning outcomes of Civics class V students at SD Negeri 12 Gedong Tataan, Gedong Tataan District in 2022